Growing grass: Lucrative opportunities in commercialization of feeds in western Kenya - International Livestock Research Institute (International Livestock Research Institute, 2019)
Beneficiaries of the Accelerated Value Chain Development (AVCD) program share how high-quality livestock fodder grasses such as Brachiaria is enabling them to double their cows’ daily milk production. More milk means more income to invest in viable enterprises. By supporting farmers with evidence-based information on feeds and fodders, farmers are able venture into the dairy sector efficiently and effectively regardless of their minimal resources. For more information about the AVCD Program visit www.avcdkenya.net